THE IMPORTANCE OF CULTURAL UNDERSTANDING IN TRANSLATION - Barchinoy, Bakhronova (PT. Antis International Publisher, 2024)
This article talks about the importance of cultural understanding in translation and gives some important aspects of cultural communication in translation.